Exploring Post Disaster Scenario in a community frequently affected by landslide using PRA Technique: A case study of Batali Hill community, Chattogram city - Kabir, Irfat; Munira, Sirazum; Das, Joynta; Ali, Md Momin; Mahfuz, Shaif Md; Raja, Debasish Roy; Das, Tandra (Journal of Bangladesh Institute of Planners, 2020)
The occurrences of the landslide at the Chattogram City Corporation Area is usual than other cities for excessive rainfall & hill cutting. The study aims to understand the post-disaster scenario due to landslide in Batali Hill community using PRA tools concerning community response of handling the difficulties. The study area Batali Hill has been chosen based on historical events & losses for being illiterate & poor respondents on that community; the Participatory Rural Appraisal techniques have been adopted to collect field data by emphasizing community capacities & effects of the landslide. To assess the situation of the community after the disaster the positive as well as the negative impacts are determined & also the extent of losses due to landslide has been determined. On the contrary, the external spatial opportunity to build strength against the disaster to influence the recovery level of the community can be determined. The losses of property, lives, injured, & other scarcities on the different seasons have been emphasized here with the role of government & non-government contribution. The broader issues in the context of all over the country have been discussed critically & the suggested strategies with impacts were based in local contexts to reduce the loses & increases community sustainability, which is not always suitable for a broader range. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 139-152